Enhancing learning through cooperative learning: UTM experience - Hassim, Mimi Haryani; Abd. Hamid, Mohd. Kamaruddin; Abu Hassan, Mohd. Ariffin; Syed Hassan, Syed Ahmad Helmi; Mohd. Yusof, Khairiyah; Esa, Mazlina (2004)
Lecture-based classes are the predominant teaching method in all levels of education. This teaching style, undoubtedly is able to deliver knowledge to students and produce graduates. However, this teaching technique is usually unable to invoke higher level of cognitive skills. With an ever-growing volume of knowledge that must be covered in engineering education, an alternative technique must be used to enhance learning. Co-operative learning is a proven teaching technique that is able to enhance students’ learning through active learning. This technique has been widely accepted in engineering education in the United States, Europe, United Kingdom and Australia. In UTM, lecturers from different faculties of engineering implement cooperative learning in their classes. The main aim is to induce better retention, in-depth understanding and mastery of knowledge among students. This paper shows how cooperative learning successfully enhance students' learning by looking at the performance of their grades in different engineering classes.